(untitled) (JSSE - Journal of Science & Sustainable Engineering, 2023)
This work analyzes the influence of some chemical steps used in standard cleaning recipes on the surface micro-roughness of silicon wafers. The effect of varying the ammonium hydroxide concentration in the NH4OH: H2O2:H2O solution was studied and silicon wafer micro-roughness was characterized by atomic force microscopy technique at different scans of 1µmx1µm. Based on the results, it was possible to point the condition to obtain low surface micro-roughness for NH4OH-based solutions with the lowest NH4OH content before the growth of gate oxides. Following, it silicon-oxide thin films were grown onto periodic rectangular shapes, 100 nm in height, obtained by localized plasma etching on silicon wafer surfaces. Silicon oxides (SiO2), about 4.5 nm thick, were grown in ultrapure dry-O2 or pyrogenic (O2 + H2) environments in order to compare the planar uniformity and the grade of coverage at the step edges of rectangular shapes defined onto silicon surfaces. Pyrogenic and conventional oxidation at 850 oC allowed one to obtain gate oxides on 100 nm-stepped silicon surfaces with high dielectric breakdown field (>10 MV/cm), good planar uniformity and conformal coverage at the step edges. The impact of this result is now the feasibility of fabricating good-quality gate oxides for surrounding gate transistors (SGT’s) and texturized MOS solar cells.